The end is always near : apocalyptic moments, from the Bronze Age collapse to nuclear near misses - Carlin, Dan, 1965- (Harper, an imprint of HarperCollinsPublishers, 2019)
"A journey back in time that explores what happened -- and what could have happened -- from creator of the wildly-popular podcast Hardcore History and 2019 winner of the iHeartRadio Best History Podcast Award"--